Rapid improvement of osseous sarcoidosis after the treatment of pulmonary aspergillosis by itraconazole - Murakami, K.; Tamada, T.; Abe, et al., K. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2011)
Osseous sarcoidosis is relatively uncommon, and treatment with corticosteroids is not always effective. Moreover, patients with an advanced stage of pulmonary sarcoidosis are sometimes infected with aspergillus in the cavities of the pulmonary lesions, and long-term use of corticosteroids should be prohibited to prevent the development of fatal invasive pulmonary aspergillosis. Here, we described a unique case of osseous sarcoidosis with pulmonary aspergillosis, showing a rapid improvement of the osseous symptoms just after the administration of the antifungal agent, itraconazole. Itraconazole is likely to become a candidate among new therapeutic agents for osseous sarcoidosis.